2004
DOI: 10.1121/1.1639330
|View full text |Cite
|
Sign up to set email alerts
|

Mode-exciting method for Lamb wave-scattering analysis

Abstract: This paper presents an innovative method, called the mode-exciting method, to solve Lamb wave-scattering problems in an infinite plate. In this method, a set of Lamb wave modes is excited by appropriate boundary conditions given on the virtual edges of a finite plate. After solving numerically the elastodynamic problem defined in the finite domain, the numerical solution is decomposed into Lamb wave modes. The Lamb wave modes constitute a system of equations, which can be used to determine the scattering coeff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 9 publications
0
34
0
Order By: Relevance
“…Similarly to the derivation shown in our previous paper, 12) it can be shown that P mn has the physical meaning as follows:…”
Section: Generalized Orthogonality Of Guided Wave Modesmentioning
confidence: 93%
See 3 more Smart Citations
“…Similarly to the derivation shown in our previous paper, 12) it can be shown that P mn has the physical meaning as follows:…”
Section: Generalized Orthogonality Of Guided Wave Modesmentioning
confidence: 93%
“…Note that since the reflection problem is a symmetric problem in the thickness direction, the symmetric and antisymmetric modes are uncoupled each other. For comparison, the results obtained by the mode-exciting method 12) are also shown by symbols. Very good agreement is found between both results.…”
Section: Normal Incidencesmentioning
confidence: 99%
See 2 more Smart Citations
“…A similar approach using SH guided waves has been proposed by Wang and Hirose. 13) In the formulation of the inverse method, the far field expressions of the Green's function for a plate waveguide are firstly deduced, and are then substituted into the integral expression of scattered waves by flaws subjected to a single incident Lamb mode. Furthermore, introducing Born approximation into the integral formula yields the Fourier transform pair between a thinning-flaw shape, which is expressed by the depth as a function of the longitudinal coordinate, and reflection coefficients in frequency domain.…”
Section: Introductionmentioning
confidence: 99%